European experience with methotrexate treatment in Crohn's disease: a multicenter retrospective analysis. Issue 7 (July 2016) - Kopylov, Uri; Katsanos, Konstantinos H.; van der Woude, Christien Janneke; Karmiris, Konstantinos; Hernandez, Vicent; Odes, Selwyn; Papamichael, Konstantinos; Koutroubakis, Ioannis E.; Bojic, Daniela; Kaimakliotis, Ioannis; Fiorino, Gionata; Papageorgiou, Neofytos; et al.
Abstract : Introduction: Methotrexate (MTX) has been utilized for the treatment of Crohn's disease (CD) for decades. Nevertheless, current data provide equivocal evidence on the efficacy of MTX in CD. The aims of this study were to describe the efficacy of MTX for maintenance of remission in CD and to identify the factors associated with the probability of steroid-free clinical remission in a multicenter European referral center cohort. Patients and methods: This was a retrospective cohort analysis. Consecutive patients treated with MTX for CD were included from 11 referral centers. Patients receiving concomitant treatment with tumor necrosis factor inhibitors or thiopurines were excluded. The main outcome was steroid-free clinical remission; the secondary outcomes included the rate of complications leading to MTX discontinuation and duration of relapse-free survival in patients achieving the main outcome. Results: Between July 1992 and January 2012, 118 patients were identified for inclusion. MTX administration route was oral for induction in 31.4% and for maintenance in 49.1% of the patients. Steroid-free remission was achieved in 44/118 (37.2%) patients and was maintained relapse free by 28/44 (63.6%) for a median of 12 (3.5–18.5) months. At least one adverse effect was reported by 28.9% of the patients. No clinical or demographic factors were associated with either likelihood of achieving a clinical response or duration of relapse-free survival. Conclusion: MTX treatment induced steroid-free clinical remission in over a third of CD patients and maintained it for a year in almost two-thirds of the responders. MTX should be considered a viable therapeutic option in CD patients refractory to other therapies.